Financial literacy: financial knowledge of Portuguese individuals - Lopes, Gonçalo José Pereira (2020)
Financial literacy is no longer a choice, but an obligation. People must be aware of the several financial issues that affect their daily lives, otherwise, they can be harmed by their decisions. The growing complexity of financial markets is originating more sophisticated financial products, therefore, individuals must possess the adequate knowledge to face these innumerous alternatives. In this context, this study aims to assess the financial literacy of Portuguese individuals, about some areas considered crucial for their financial well-being. It is important to understand the savings and investing habits of individuals, to identify their knowledge regarding credit and interest rates, as well as to identify their risk tolerance towards investing. A survey was conducted in 2020 (January - April), in order to obtain the necessary evidence for the study. The questions included several topics, thus enabling to collect data from different financial areas, such as savings, securities or interest rates. The sample comprises 240 Portuguese individuals, from 18 to 69 years old. The results show that the level of effective knowledge of participants is below 50%, which clearly represents an inadequate outcome. These results are in line with previous studies, thus meaning that even though there have been implemented specific programs focused on incrementing the financial knowledge of individuals, they still do not possess the necessary financial literacy that is required.